2021
DOI: 10.3389/fmed.2021.712918
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Treatments for Patients With Portal Hypertension and Cirrhosis: A Systematic Review and Bayesian Network Meta-Analysis

Abstract: Background and Aims: Viral hepatitis are one of the main causes of liver cirrhosis. The treatment of portal hypertension caused by liver cirrhosis is difficult and diverse, and the therapeutic effect is unknown. Bayesian network meta-analysis was performed to compare the efficacy and safety of treatments for patients with portal hypertension and cirrhosis, including a transjugular intrahepatic portosystemic shunt (TIPS), endoscopic therapy, surgical therapy and medications.Methods: Eligible articles were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(46 reference statements)
1
3
0
2
Order By: Relevance
“…The findings of this systematic review indicated that the entire literature confirmed the excellent efficacy, safety, and clinical outcomes of splenorenal shunt surgery in patients with portal hypertension. The aforementioned results are consistent with the meta-analysis conducted by Yao et al (2021), who revealed that transjugular intrahepatic portosystemic shunts and distal splenorenal shunts exhibited a greater capacity to decrease rebleeding rates when compared to other therapeutic approaches. Several other studies have indicated that the use of mixed treatments may (Gómez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of this systematic review indicated that the entire literature confirmed the excellent efficacy, safety, and clinical outcomes of splenorenal shunt surgery in patients with portal hypertension. The aforementioned results are consistent with the meta-analysis conducted by Yao et al (2021), who revealed that transjugular intrahepatic portosystemic shunts and distal splenorenal shunts exhibited a greater capacity to decrease rebleeding rates when compared to other therapeutic approaches. Several other studies have indicated that the use of mixed treatments may (Gómez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…These complications had a significant impact on the prognosis and clinical outcomes of splenorenal shunt surgery. A broad range of therapeutic options were widely used, spanning from pharmacological to nonpharmacological interventions (Gairing et al 2021, Yao et al 2021. The pharmacological intervention exhibits favourable effectiveness in the short-term management of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У большинства пациентов (58,82%) по результатам ЭФГС ВРВП исчезли и уменьшились до I степени. Тромбоз шунта возник у двух больных из двадцати через 7 и 10 лет, что согласуется с данными литературы [11].…”
Section: Discussionunclassified
“…The main purpose of treatment is to control symptoms and finally prevent progression to cirrhosis and/or PH. Reached this stage, the management of patients can be similar to that of other causes of cirrhosis and/or PH, including medical treatment such as β-blockers, sclerotherapy of esophageal variceal, or TIPS ( 40 ). Yao et al studied the efficacity of TIPS for non-cirrhotic PH over 25 patients, including three patients with sarcoidosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%